GPU Acceleration of VOLEitH-Based Post-Quantum Signatures: A Reusable Fragment-Graph Framework - Shyba, Victor; Custódio, Ricardo Felipe (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
Post-quantum digital signature schemes based on the Vector Oblivious Linear Evaluation in the Head (VOLEitH) paradigm represent a promising direction in the NIST Post-Quantum Cryptography standardization process for additional digital signatures. FAEST, an AES-based scheme, was selected for the third round in May 2026 [Alagic et al. 2026]; PERK, based on the Permuted Kernel Problem, was not selected but adopted the VOLEitH framework and serves here as an architectural case study. To the best of our knowledge, this is the first reported GPU implementation of a VOLEitH-based signature pipeline. This paper presents the design, implementation, and evaluation of a reusable GPU framework for VOLEitH-based signatures, implemented in CUDA and applied to FAEST and PERK. The architecture adopts a fragment-graph model over caller-owned workspaces, covering seed expansion via AES-CTR, GGM tree construction, BAVC commitments, VOLE operations, and scheme-specific stages. Experiments on an NVIDIA H100 GPU report throughput of up to 34,026 sig/s for FAEST-128f and speedups of 1.23×–2.77× for signing and 1.99×–7.59× for verification over a normalized 16-worker AVX CPU baseline across all six FAEST v2 variants. The PERK GPU implementation achieves a speedup of 5.65×–9.64× in signing speed under the same methodology, providing empirical evidence of the developed infrastructure.